Endothelial Glycocalyx Layer Properties and Its Ability to Limit Leukocyte Adhesion - Delgadillo, Luis F. (Biophys J, 2020)
The endothelial glycocalyx layer (EGL), which consists of long proteoglycans protruding from the endothelium, acts as a regulator of inflammation by preventing leukocyte engagement with adhesion molecules on the endothelial surface. The amount of resistance to adhesive events the EGL provides is the result of two properties: EGL thickness and stiffness. To determine these, we used an atomic force microscope to indent the surfaces of cultured endothelial cells with a glass bead and evaluated two different approaches for interpreting the resulting force-indentation curves. In one, we treat the EGL as a molecular brush, and in the other, we treat it as a thin elastic layer on an elastic half-space. The latter approach proved more robust in our hands and yielded a thickness of 110 nm and a modulus of 0.025 kPa. Neither value showed significant dependence on indentation rate. The brush model indicated a larger layer thickness (∼350 nm) but tended to result in larger uncertainties in the fitted parameters. The modulus of the endothelial cell was determined to be 3.0–6.5 kPa (1.5–2.5 kPa for the brush model), with a significant increase in modulus with increasing indentation rates. For forces and leukocyte properties in the physiological range, a model of a leukocyte interacting with the endothelium predicts that the number of molecules within bonding range should decrease by an order of magnitude because of the presence of a 110-nm-thick layer and even further for a glycocalyx with larger thickness. Consistent with these predictions, neutrophil adhesion increased for endothelial cells with reduced EGL thickness because they were grown in the absence of fluid shear stress. These studies establish a framework for understanding how glycocalyx layers with different thickness and stiffness limit adhesive events under homeostatic conditions and how glycocalyx damage or removal will increase leukocyte adhesion potential during inflammation.